2017
DOI: 10.1371/journal.pone.0172549
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Wnt/β-catenin signaling in blood cells of patients with severe cavitary pulmonary tuberculosis

Abstract: Tuberculosis (TB) remains as a leading infectious disease worldwide. Our previous study showed interferon (IFN)-γ and CD3 T cell impairment in patients with severe cavitary pulmonary TB (PTB). However, the cause of the change in immune responses during the progression of TB is still poorly understood. In this study, eight newly diagnosed patients with severe cavitary and mild lesion non-cavity PTB were recruited, and three healthy volunteers were recruited as the control. RNA extracted from blood was tested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…The present TB study showed that β -catenin in both CD4 + and CD8 + T cells had a close association with the regulation of TB progress. Increased β -catenin can enhance the expression of Th1 responses in the CD4 + T population, which is consistent with our previous study [ 15 ]. Interestingly, the frequency of IFN- γ in CD4 + T cells was significantly increased in PBMCs of PTB patients after LiCl stimulation compared with before LiCl stimulation ( Figure 5(c) ), while IFN- γ measurements by ELISA of PTB patients' PBMCs did not show differences between before and after LiCl stimulation ( Figure 5(e) ), indicating that increased β -catenin did not enhance the whole IFN- γ secretion but IFN- γ secretion from some kinds of cells such as CD4 + T cells in the PBMCs of PTB patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present TB study showed that β -catenin in both CD4 + and CD8 + T cells had a close association with the regulation of TB progress. Increased β -catenin can enhance the expression of Th1 responses in the CD4 + T population, which is consistent with our previous study [ 15 ]. Interestingly, the frequency of IFN- γ in CD4 + T cells was significantly increased in PBMCs of PTB patients after LiCl stimulation compared with before LiCl stimulation ( Figure 5(c) ), while IFN- γ measurements by ELISA of PTB patients' PBMCs did not show differences between before and after LiCl stimulation ( Figure 5(e) ), indicating that increased β -catenin did not enhance the whole IFN- γ secretion but IFN- γ secretion from some kinds of cells such as CD4 + T cells in the PBMCs of PTB patients.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the protein level of β -catenin in the whole cell can be associated with the activation of the canonical Wnt/ β -catenin pathway. Our previous study showed that β -catenin mRNA in CD14 − cells was impaired in severe PTB patients, and stimulation of β -catenin could enhance the activation of CD4 + T cells in the blood of PTB [ 15 ]. In the present study, the frequency of CD4 + T cells in conditional Ctnnb1 −/− infected mice was decreased, indicating a role of β -catenin in the activation and proliferation of CD4 + T cells of hosts infected with TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore critical to maintain the cellular immune response balance. 4 To achieve this balance, the host uses some strategies, such as producing cytokines, to monitor and mediate effector cell function. 5 Cytokines are important in cell signaling and can affect the behavior of adjacent cells.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry was performed as described in the other reports [26,27]. 0.1 Million H1975 cells was rstly plated in 24-well-plate.…”
Section: Intracellular Cytokine Staining (Ics) For T Cell Activation mentioning
confidence: 99%